Re-emergence of Lassa fever disease: the theory of interepidemic effect in action - Obasi, C.; Didigwu†, N.; Laminu‡, I. (International Journal of Mathematical Analysis and Modelling, 2023)
The Lassa fever virus is one of several viruses that are likely to cause a future epidemic as reported by WHO due to re-emergence. The re-emergence of Lassa fever is due to the phenomenon called interepidemic effect. According to the current status of the interepidemic effect, any public health control measure taken to reduce the basic reproduction number will definitely make the disease to take a very long time to re-emerge. This short expository note establishes the fact that the reemergence of Lassa fever disease is actually the theory of interepidemic effect in action.